Evaluation of Articular Cartilage Progenitor Cells for the Repair of Articular Defects in an Equine Model. (18th March 2015) - Frisbie, David D.; McCarthy, Helen E.; Archer, Charles W.; Barrett, Myra F.; McIlwraith, C. Wayne
Abstract : Background: We sought to determine the effectiveness of chondroprogenitor cells derived from autologous and allogenic articular cartilage for the repair of cartilage defects in an equine model. Methods: Cartilage defects (15 mm) were created on the medial trochlear ridge of the femur. The following experimental treatments were compared with empty-defect controls: fibrin only, autologous chondroprogenitor cells plus fibrin, and allogenic chondroprogenitor cells plus fibrin (n = 4 or 12 per treatment). Horses underwent strenuous exercise throughout the twelve-month study, and evaluations included lameness (pain) and arthroscopic, radiographic, gross, histologic, and immunohistochemical analyses. Results: Arthroscopy and microscopy indicated that defects in the autologous cell group had significantly better repair tissue compared with defects in the fibrin-only and control groups. Repair tissue quality in the allogenic cell group was not superior to that in the fibrin-only group with the exception of the percentage of type-II collagen, which was greater. Radiographic changes in the allogenic cell group were poorer on average than those in the autologous cell group. Autologous cells significantly reduced central osteophyte formation compared with fibrin alone. Conclusions: On the basis of the arthroscopic, radiographic, and histologic scores, autologous cells in fibrin yielded better results than the other treatments; allogenic cells cannot be recommended at this time. Clinical Relevance: Autologous chondroprogenitor cells in fibrin appeared to yield a modest improvement over fibrin alone, with a 128% difference in central osteophyte formation compared with fibrin-only treatment. This cell type may show clinical benefit, and comparisons with other cartilage resurfacing techniques should be considered.